Analisis Implementasi Kurikulum Merdeka di Sekolah Dasar - Qiftiyah, Maratul; Hidayati, Atika Nur (Al Banin : Jurnal Ilmiah Pendidikan Dasar, 2024)
Abstract The problem of this research lies in a holistic approach. It focuses on the analysis of the implementation of the independent curriculum by exploring aspects of implementation strategies, challenges faced, and their impact on student learning. This study aims to analyze the implementation of the independent curriculum at SDN 1 Sumber Agung. The qualitative approach is descriptive, with data collection through interviews, observations, and document analysis. The study results indicate that SDN 1 Sumber Agung has implemented an independent curriculum with a thematic approach, project-based learning, and formative assessment. However, the challenges faced include the lack of teacher understanding of the concept of the independent curriculum, limited learning resources, and resistance from several parties to changes in learning practices. Based on the results of the study, the implementation of the independent curriculum at SDN 1 Sumber Agung showed a positive impact on student learning, especially in increasing engagement, critical thinking skills, and collaboration through project-based learning. This study also identified that the success of implementation is highly dependent on effective teacher training, support from the principal, and the active involvement of all related parties. Therefore, efforts are needed to strengthen teacher competence and ongoing mentoring so that the implementation of the independent curriculum can be more optimal.